2017
DOI: 10.1590/1980-5373-mr-2017-0556
|View full text |Cite
|
Sign up to set email alerts
|

Selective Surfaces of Black Chromium for Use in Solar Absorbers

Abstract: One of the applications of selective surfaces is to improve performance of solar absorbers. The purpose of this work is to produces selective coatings with high absorption of solar radiation in the range of UV/Vis/NIR. It was prepared a selective surface composed of black chromium (Cr/Cr 2 O 3 ) deposited on substrates of AISI 304 stainless steel using the technique of electrolytic deposition for application in solar thermal absorbers. The great parameters for deposition consisted of a continuous electric curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 10 publications
0
12
0
2
Order By: Relevance
“…Os resultados obtidos corroboram com os estudos de Nunes et al (2018) que ao aplicarem a técnica de difração de raios-x em amostras de cromo eletrodepositadas sobre substratos de aço inoxidável AISI 304 seguido de um tratamento térmico a 600ºC por duas horas, observaram a formação das fases correspondentes ao cromo metálico e ao Cr 2 O 3 . Assim como nos resultados obtidos nesse trabalho, Nunes et al (2018) também não identificaram a presença de Cr 3 O nos padrões de difração das amostras submetidas a tratamento térmico, fato que pode ser explicado pela transformação dessa fase em uma fase mais estável (Cr 2 O 3 ) durante esse processo. A formação de Cr 2 O 3 está diretamente relacionada com a qualidade dos filmes depositados.…”
Section: Difração De Raios-xunclassified
See 1 more Smart Citation
“…Os resultados obtidos corroboram com os estudos de Nunes et al (2018) que ao aplicarem a técnica de difração de raios-x em amostras de cromo eletrodepositadas sobre substratos de aço inoxidável AISI 304 seguido de um tratamento térmico a 600ºC por duas horas, observaram a formação das fases correspondentes ao cromo metálico e ao Cr 2 O 3 . Assim como nos resultados obtidos nesse trabalho, Nunes et al (2018) também não identificaram a presença de Cr 3 O nos padrões de difração das amostras submetidas a tratamento térmico, fato que pode ser explicado pela transformação dessa fase em uma fase mais estável (Cr 2 O 3 ) durante esse processo. A formação de Cr 2 O 3 está diretamente relacionada com a qualidade dos filmes depositados.…”
Section: Difração De Raios-xunclassified
“…Entretanto, poucos autores têm discutido a utilização de tratamentos térmicos pós-deposição, que simulem o envelhecimento das superfícies, e analisem o comportamento dos óxidos de cromo, quando submetidos a esses tratamentos (PETTIT, 1983;GAO et al, 2016, ZHANG et al, 2017. Segundo Nunes et al (2018) o pós-tratamento térmico facilita a obtenção de óxidos de cromo, que está diretamente relacionado com a qualidade dos filmes obtidos, e um aumento da absortância.…”
Section: Introductionunclassified
“…Many methods had been used to prepare selective absorbers, such as electrodeposition, sputtering, evaporation, pyrolysis, painting and sol-gel 7 . This study opted for the use of the electrodeposition technique due to the simplicity of the equipment used and its low cost, the good optical proprieties (absorptance and emittance) of the obtained coatings, in addition to the technique being able to the realized at ambient temperature and atmospheric pressure, which makes it particularly attractive for industrial applications 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Cheng et al [5] presented a photoexcited switchable absorber composed of X-shaped gold structures and a silicon pad. Nunes et al [24] demonstrated a selective surface composed of black chromium (Cr/Cr 2 O 3 ) deposited on substrates of AISI 304 stainless steel for solar heat absorption. Tian et al proposed a one-dimensional HfO 2 / Al 2 O 3 -W nanocomposites/W/Al 2 O 3 /W multilayered photonic structure as potential wavelength-selective thermal devices.…”
Section: Introductionmentioning
confidence: 99%